Dance in thumri - Banerji, Projesh (New Delhi : Abhinav Publications, 1986)
On the thumri style in Hindustani school of music, romantic and devotional in temperament, with introduction to the vocalists and dancers of the genre and Thumri dance-songs in Hindi and English.
Includes index.
Discography: p. [105]-112.
Keywords: Theater -- India -- History; Performing arts -- India -- History; Indic drama -- History and criticism; Dance -- India